Assisted ventilation in severe acute asthma. Issue 6 (June 1986) - Higgins, B; Greening, A P; Crompton, G K
Abstract : During the period 1973-85 assisted ventilation was used for the treatment of severe asthma on 48 occasions in 18 patients (one patient was ventilated 29 times). On each occasion arterial blood gas abnormalities were restored to normal as quickly as possible irrespective of peak inflation pressures. One patient was thought to be brain dead on transfer from another hospital but was ventilated for 48 hours while this diagnosis was confirmed. There was one episode of mediastinal emphysema. There were no other complications apart from transient hypotension (blood pressure less than 100/60 mm Hg), which occurred on 17 occasions but did not have any sequelae. There was no relationship between hypotension and inflation pressure but there was an association between hypotension and rate of fall of arterial carbon dioxide tension. It is concluded that the risks of barotrauma during the ventilation of patients with severe asthma are theoretical or extremely small. Rapid correction of respiratory acidosis abolishes hypercapnic respiratory drive, allowing ventilation without use of muscle relaxants. It may also enable a shorter duration of ventilation, thus decreasing the likelihood of complications.